MODALITAS ~SOUDA, ~YOUDA, DAN ~RASHII DALAM KALIMAT BAHASA JEPANG - Hasanah, Niswatul; Astuti, Sri Puji; Rosliana, Lina (Japanese Literature, 2015)
This research title is ‘Modality in the form of ~souda, ~youda, and ~rashii in Japanese sentences’. The writer chose the title due to the lack of explanation of those words in Japanese books, therefore there were still many mistakes in using ~souda, ~youda, and ~rashii. The first step in writing this thesis was collecting the data by the writer, analyzed the data, and presented the data descriptively. ~Souda, ~youda, and ~rashii in Indonesian mean sepertinya or tampaknya and it indicates approximation modality, meanwhile ~souda and ~rashii function as quotation modality. Although in Indonesian those three words can be interpreted with a same word, there are actually differences in meaning and usage of those words.~Souda in approximation modality states assumption, supposition or speculation based on visual information. In quotation modality, ~souda functions to deliver news heard from the others. ~Youda is used when the speaker wants to express assumption, supposition or speculation based on information received by the senses according to its subjective valuation. ~Rashii in approximation modality tells an assumption or speculation objectively based on almost certain validity. In the other hand, ~rashii in quotation modality is used to convey information or opinion according to fact or information. The fact is obtained through observation or other resources.